Revenue Collection and Division-Wise National Budget Allocation of the Government of Bangladesh - Mehedi Hasan Manik (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bangladesh is a developing country, but its inequality is increasing gradually due to improper budget allocation. This study is conducted to evaluate revenue collection, the national budget along with the division-wise allocation in Bangladesh. Data for this study has been collected from the websites of the finance ministry and Bangladesh Bureau of Statistics. From the tax sector, Bangladesh collected 81.5% of revenue in 2021 and has planned to collect 88.9% in 2023. The government is expecting more earnings from the tax sector. The budget deficit of the country was -28.1% of expenses in 2021 and might be 35.7% of expenses in 2023. The increasing budget deficit is creating a fiscal burden on the economy. The country spent 18.7%, 14.8%, and 12.0% in public service, education, and interest payment, respectively, in the revised budget for 2022. Bangladesh should increase the budget allocation in agriculture, health, and housing sectors to promote sustainable development, and it should cut allocation in interest payment, public service, and defense sectors to reduce the budget deficit. Policymakers of Bangladesh may use this study to the allocate national budget and collect revenue in the future. The study considered the total expense of 15 divisions, so further study is required involving operating and developing expenses among different sub-divisions for a better understanding of the national budget allocation of Bangladesh.